2009
DOI: 10.1017/s1462399409001082
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion ofPlasmodium falciparum-infected erythrocytes to human cells: molecular mechanisms and therapeutic implications

Abstract: Severe malaria has a high mortality rate (15–20%) despite treatment with effective antimalarial drugs. Adjunctive therapies for severe malaria that target the underlying disease process are therefore urgently required. Adhesion of erythrocytes infected with Plasmodium falciparum to human cells has a key role in the pathogenesis of life-threatening malaria and could be targeted with antiadhesion therapy. Parasite adhesion interactions include binding to endothelial cells (cytoadherence), rosetting with uninfect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
354
0
20

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 338 publications
(376 citation statements)
references
References 223 publications
(308 reference statements)
2
354
0
20
Order By: Relevance
“…Evidence from previous studies have shown that haem, the substrate of HO‐1, is also its major inducer 15, 16, 17, 20, 33, and when cells are exposed to haem there is an increased expression of HO‐1 to catabolize haem and prevent its cytotoxicity 33. As patients with the HbAS genotype have higher levels of haem compared with HbAA genotype at convalescence, we investigated the possibility of a corresponding induction of HO‐1 in both genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from previous studies have shown that haem, the substrate of HO‐1, is also its major inducer 15, 16, 17, 20, 33, and when cells are exposed to haem there is an increased expression of HO‐1 to catabolize haem and prevent its cytotoxicity 33. As patients with the HbAS genotype have higher levels of haem compared with HbAA genotype at convalescence, we investigated the possibility of a corresponding induction of HO‐1 in both genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Los receptores más importantes son la glucoproteína CD36 y la molécula 1 de adhesión intercelular (Intercellular Adhesion Molecule 1, ICAM-1) en el endotelio y el sulfato A de condroitina (Chondroitin Sulfate A, CSA) en placenta. Otros receptores incluyen la molécula 1 de adhesión vascular (Vascular Cell Adhesion Molecule 1, VCAM-1) y la E-selectina en endotelio, las proteínas PCAM-1/ CD31 en plaquetas y endotelio, el sistema de antígenos ABO, el sulfato de heparán y el receptor 1 del complemento (CR1) en eritrocitos no parasitados (8). Bajo condiciones fisiológicas, el secuestro puede obedecer a una interacción con múltiples receptores y en parásitos aislados se han observado fenotipos multiadhesivos que se asocian con enfermedad grave (3,8,9).…”
Section: Receptores Implicados En La Adherenciaunclassified
“…La unión a este receptor es común en parásitos aislados en diferentes países de África (9,11,12), Thailandia (13,14) y Brasil (10). La relación entre el CD36 y la gravedad clínica es controversial; en general, se asocia este receptor con enfermedad no complicada (8,9,11,13 …”
Section: Receptores Implicados En La Adherenciaunclassified
See 2 more Smart Citations